A Rare Case of Naviculo-medial Cuneiform Coalition Treated with Naviculo-medial Cuneiform Arthrodesis: A Case Report. Issue 2 (24th April 2023) - Feeney, Kaylem M.; Kearns, Stephen R
Abstract : Case: A 19-year-old woman developed spontaneous onset of right midfoot pain in the absence of trauma. Conservative management including orthotics and steroid injection reduced, but did not resolve, pain. Weight-bearing x-ray and CT confirmed naviculo-medial cuneiform coalition. After failure of conservative treatment, the patient elected to undergo right naviculo-medial cuneiform arthrodesis and returned to normal activity without pain postoperatively and at 4-year follow-up. Conclusion: Naviculo-medial cuneiform coalition is a rare source of midfoot pain, but should be considered as a differential diagnosis. This case suggests that naviculo-medial cuneiform arthrodesis can successfully resolve symptoms if conservative measures fail.